HGF, sIL-6R and TGF-β1 Play a Significant Role in the Progression of Multiple Myeloma - Jurczyszyn, Artur; Czepiel, Jacek; Biesiada, Grażyna; Gdula-Argasińska, Joanna; Cibor, Dorota; Owczarek, Danuta; Perucki, William; Skotnicki, Aleksander B (Journal of Cancer, 2014)
Background. In the last few years, it has been widely reported that proinflammatory and angiogenic cytokines are important for the development and progression of multiple myeloma (MM). Objectives. To further validate and acquire more insight into this view we decided to check whether plasma levels of certain cytokines and their soluble receptors differ between MM patients and healthy subjects. Patients and Methods. The study was conducted in 76 MM patients aged 22 to 77 years (60±10 years) and 35 healthy controls aged 20 to 63 years (33±10 years). Plasma levels of interleukin-6 (IL-6), b-fibroblast growth factor (b-FGF), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1), as well as soluble receptors for IL-6 (sIL-6R) and VEGF (sVEGF-R2) were measured using enzyme-linked immunosorbent assay (ELISA). Results. Significantly higher plasma levels of IL-6 (13.65±42.61 vs. 1.04±1.12 pg/ml, p=0.006), HGF (2174±2714 vs. 648±130 pg/ml, p<0.001), b-FGF (7.92±10.78 vs. 2.54±5.38 pg/ml, p<0.001) and sIL-6R (37.1±14.2 vs. 25.3±6.4 ng/ml, p=0.003) were observed in MM patients vs. healthy controls, respectively. Plasma sVEGF-R2 was significantly lower in MM patients than in controls (7518±2119 vs. 8725±1281 pg/ml, respectively; p<0.001). We observed an inverse correlation between length of treatment and the level of sIL-6R, and TGF-β1 in plasma. Conclusions. Plasma levels of HGF, b-FGF, IL-6 and sIL-6R in MM patients were higher ​​when compared to the control group. Antineoplastic therapy leads to a time-dependent decrease in plasma levels of sIL-6R, and TGF-β1 in MM patients. Blood plasma level of HGF is an optimal measure to differentiate patients in whom disease is progressing versus patients who respond to therapy.